KONTRAK SOCIAL JOHN LOCKE ANTARA NEGARA DAN MASYARAKAT DALAM UU NO. 18 TAHUN 2019 TENTANG PESANTREN - Arianto (Jurnal Ilmu Hukum, 2023)
ABSTRACT For John Locke no one can have political power without the consent of the people. This means that essentially all people's activities will be determined by the people's approval. However, only free humans (not slaves) who agree to think and act in one sovereign government are referred to as civil society. It is this government that then has the duty to protect life, freedom, and people's property. The relationship between politics and law is very intimate, law is a statutory regulation which is actually the crystallization of political wills that interact and influence each other. Legal politics is defined as the official line of state policy to make and stipulate laws and regulations in order to achieve the goals and objectives of the state as contained in the preamble of the 1945 Constitution of the Republic of Indonesia, paragraph IV. One of the manifestations of the state's alignment is realizing the mandate of the constitution into regulations that are pro-people. Islamic boarding schools have an important role in various aspects of national life. 18 of 2019 are: State access and recognition of Islamic boarding schools, maintaining national commitment, recognition of Islamic boarding schools' academic traditions, maintaining the uniqueness of Islamic boarding schools, maintaining the independence of Islamic boarding schools. This research is a qualitative research with a juridical analysis approach. This objective aims to understand the direction of State policy and the State's alignment with Islamic boarding schools in terms of Jean Jacquess Rousseau's social contract which was passed in UU.No.18 of 2019. Keywords: Social contract, state, Islamic boarding school.